Revealing the Mineralogical and Petrographic Signs of Fluid-Related Processes in the Kelebia Basement Area (Szeged Basin, S Hungary): A Case Study of Alpine Prograde Metamorphism in a Permo-Triassic Succession - Andrea Varga; Elemér Pál-Molnár; Béla Raucsik (Geofluids)
The Szeged Basin (S Hungary) occupies a relatively central position within the European Alpine–Carpathian–Dinaride orogenic belt. An ongoing controversy about the tectonic position of the study area indicates that its evolution is still not fully understood; however, several important hydrocarbon occurrences are known in the fractured basement reservoirs. The main aim of this contribution is to investigate the petrographic features and possible Alpine metamorphic conditions of volcanic/volcanoclastic and siliciclastic rocks from the Kelebia basement area. Due to the outcrop conditions and poor exposure, study samples are obtained from cores and core chips resulting from oil exploration. Based on an evaluation of petrographic (including also cathodoluminescence analysis) and microstructural features, joined with mineralogical and metamorphic data such as “illite crystallinity” and K-white mica crystallite size obtained by X-ray powder diffractometry (XRPD), a very low- to low-grade (ca. 300°C) Alpine metamorphic imprint of this portion of the basement can be proposed. Several deformation characteristics (deformation lamellae in quartz, deformation twins in dolomite, fragmented porphyroclasts, and strain shadows) were recognized in the studied samples, showing a weakly to moderately developed disjunctive foliation in the Permian rocks, as well as quartz veinlets, microcracks, and fluid inclusion planes in the Lower Triassic sandstones. Most likely, one of the Cretaceous orogenic events, namely, the “Turonian” phase (Early–Late Cretaceous nappe stacking), resulted in the prograde greenschist facies metamorphism in the study area, instead of the burial depth. We propose that the Permo-Triassic cover succession was also affected by shearing episodes accompanied by fluid migrations along the contact zone between the tectonic units. The scientific approach and dataset provided here are examples of how the application of XRPD parameters of phyllosilicates and micropetrographic observations can help to understand the evolution of an orogen and improve knowledge about the basement structure.